Effects of Confinement on Reaction‐Induced Fracturing During Hydration of Periclase. (18th August 2018) - Zheng, Xiaojiao; Cordonnier, Benoît; Zhu, Wenlu; Renard, François; Jamtveit, Bjørn
Abstract: Hydration of a nominally dry rock can cause expansion of the solid volume, resulting in reaction‐induced fracturing and an associated increase in the porosity and permeability of the rock. We study the effect of confinement on the coupling between stress generation, reaction‐induced fracturing, and porosity evolution during the hydration of periclase (MgO) into brucite (Mg(OH)2 ). Samples of a microporous MgO ceramic were hydrated at 170–210 °C, 5–80 MPa confining pressure, 6–95 MPa differential stress, and 5–75 MPa pore fluid pressure in a purpose‐designed triaxial load cell. Hydration‐induced changes were recorded in situ by X‐ray microtomographic imaging at 5‐min intervals. Below 30 MPa effective mean stress, the fraction of periclase replaced by brucite is a sigmoidal function of time. After a slow start, the replacement rate picks up with concomitant intense fracturing. The porosity increase resulting from the reaction‐induced fractures is transient (pulse‐like). Following the porosity pulse the rate of replacement declines until the replacement is almost complete. Above 30 MPa, the reaction rate is slow, porosity decreases monotonically without any observable fracturing during the time of the experiment. At these stress conditions, the lack of fracturing cannot be limited by the thermodynamic affinity of the reaction. A possible interpretation is that the stress generated by the reaction may overcome the disjoining pressure at the grain‐grain interface, expelling the water film trapped there and thereby dramatically reducing the reaction rate. Key Points: Time‐resolved in situ X‐ray microtomography allows imaging of reaction‐induced fracturing Reaction‐induced fracturing is associated with a transient porosity pulse Reaction‐induced fracturing slows down considerably when the effective mean stress exceeds a certain threshold